QUALITY ASSURANCE FOR DISTRIBUTIVE TEACHER EDUCATION IN NIGERIA THROUGH INFORMATION AND COMMUNICATION TECHNOLOGY (NAU Journal of Technology and Vocational Education, 2024)
This paper is an attempt to show how teachers have been trying to achieve thestandards given by the National Universities Commission (NUC) for the graduation ofdistributive education teachers. However, since the emergence of the use of informationtechnology in Nigerian business transactions, emphasis should have shifted to computerbased pedagogy to replace standards driven and teacher centred curricula. This paper arguesthat student-centred approach by which students select goals, timelines, assessment and havemuch more computer based practicals will motivate students much more, offer them moreopportunities to carry out their own projects of study and prepare them better for selfemployment. The paper recommends various measures (such as workshops for businesseducation teachers and professional accreditation visitation of university teachers) beforereaccreditations. Recognition for teachers that have ICT abilities to facilitate effective andqualitative distributive teacher education in Nigeria, will help to provide quality assurance.